Proses Pembuatan Megalitik Nias Sebagai Bagian Sistem Upacara Owasa ( Studi Kasus Proses Sebagai Sebuah Sistem Upacara Owasa di Situs Megalitik Orahili Fau) - Ketut Wiradnyana (Berkala Arkeologi Sangkhakala, 2008)
AbstractThe Nias Island is known to possess many relics in the megalithic tradition, in various forms – decorative and non decorative motifs, that emerged some questions about the material of megalithic relics, how to bring the large objects, where they did, what kind of tool they used. The process of making megalithic objects is a system who finally becaming as culture until now a megalithic.